(untitled) (Global Journal of Human-Social Science, 2020)
The fact is that practice of giving exlusive breastfeeding has not reached favorable numberin some developing countries because of various factors. This study aims to determine the relationship between the level of education of mothers, the occupation of mothers, and social support for mothers and breastfeeding behavior. The important hypothesis of this study, therefore, is that aspects of economy, environment, social, culture, and politics can influence mothers to breastfeed their babies. Secondary data from the Indonesian Family Life Survey (IFLS) 5 in 2014was employed. The total sample in this study was 5,108 people. STATA software version 13.0 with a probity model was used to analyze the data. Statistical test technique usingChi-square (X2) and multiple linear regressions were conducted. Results of this study indicate that there is no relationship between the level of education of mothers, and the occupation of mothers and breastfeeding behavior. However, there is a strong relationship between social support and breastfeeding behavior. Therefore, this study suggests that there is a need to develop the capacity of traditional midwives in order to increase the prevalence of women for breastfeeding.